Kajian Dialektis dalam Komunikasi Perawat-Pasien: Memahami Variasi Bahasa dalam Konteks Perawatan Kesehatan - Rudi Purwana; Mariana Mariana; Asrul Asrul; Afina Muharani Syaftriani; Ani Rahmadhani Kaban (Pusat Riset dan Inovasi Nasional, 2022)
This study explores the dialectical aspects of communication between nurses and patients, focusing on understanding language variations in the context of healthcare. Language variation often plays a crucial role in nurse-patient interactions, influencing understanding, compliance, and the quality of care. Through a critical discourse analysis approach, this study attempts to dissect the dynamics of communication that occur, identifying conflicts and misunderstandings that may arise due to language differences. By understanding these dialectical aspects, it is hoped that more effective and responsive communication strategies can be developed in nursing practice. The findings from this research are expected to provide valuable insights for healthcare practitioners in understanding and addressing cross-cultural communication challenges in the context of care.